Screening, referral and treatment for depression in patients with coronary heart disease. Issue 9 (20th May 2013) - Colquhoun, David M; Bunker, Stephen J; Clarke, David M; Glozier, Nick; Hare, David L; Hickie, Ian B; Tatoulis, James; Thompson, David R; Tofler, Geoffrey H; Wilson, Alison; Branagan, Maree G
Summary: In 2003, the National Heart Foundation of Australia position statement on "stress" and heart disease found that depression was an important risk factor for coronary heart disease (CHD). This 2013 statement updates the evidence on depression (mild, moderate and severe) in patients with CHD, and provides guidance for health professionals on screening and treatment for depression in patients with CHD. The prevalence of depression is high in patients with CHD and it has a significant impact on the patient's quality of life and adherence to therapy, and an independent effect on prognosis. Rates of major depressive disorder of around 15% have been reported in patients after myocardial infarction or coronary artery bypass grafting. To provide the best possible care, it is important to recognise depression in patients with CHD. Routine screening for depression in all patients with CHD is indicated at first presentation, and again at the next follow‐up appointment. A follow‐up screen should occur 2–3 months after a CHD event. Screening should then be considered on a yearly basis, as for any other major risk factor for CHD. A simple tool for initial screening, such as the Patient Health Questionnaire‐2 (PHQ‐2) or the short‐form Cardiac Depression Scale (CDS), can be incorporated into usual clinical practice with minimum interference, and may increase uptake of screening. Patients with positive screening results may need further evaluation. Appropriate treatment should be commenced, and the patient monitored. If screening is followed by comprehensive care, depression outcomes are likely to be improved. Patients with CHD and depression respond to cognitive behaviour therapy, collaborative care, exercise and some drug therapies in a similar way to the general population. However, tricyclic antidepressant drugs may worsen CHD outcomes and should be avoided. Coordination of care between health care providers is essential for optimal outcomes for patients. The benefits of treating depression include improved quality of life, improved adherence to other therapies and, potentially, improved CHD outcomes.